On the Use of Terminology of Horse Tack in the Mongolian language (Mongolian Journal of Applied Linguistics, 2023)
The article discusses words and phrases in the Mongolian language that denote equine equipment and equipment associated with the capture, tying horses, feeding them, as well as words used in various kinds of equipment for carts, harnesses, chariots, sledges, etc., using sociolinguistic questionnaires and calculations. In this study, we conducted a survey among cattle breeders in Asgat, Bayandelger and Munkhkhaan sums of Sukhbaatar aimag in 2021; and also in Batshireet sum of the Khentii aimag, in Tsagaandelger sum of the Dundgobi aimag, in Ulgii sum of the Uvs aimag in 2022 on the knowledge of vocabulary and the use of equipments for animal husbandry. We also conducted a questionnaire survey among buyers and sellers of livestock equipment at the Narantul International Trade Center in Ulaanbaatar to clarify their vocabulary and market demand for livestock equipment sold on the market in 2022. In this regard, analytical studies of vocabulary related to equipment of animal husbandry were carried out among advertisements for purchase and sale in media and other media, such as unegui.mn facebook, etc. Thus, the study showed that the knowledge of the language of cattle breeders on the equipment used in animal husbandry, differed depending on factors such as the region in which the respondents lived and their ages. Also, a study confirms that with the development of the progressiveness of society, new forms of names have appeared, which, based on the method of use, related to the peculiarity of the materials used for the manufacture of certain equipment relating to animal husbandry.Монгол хэлэн дэх адууны тоног хэрэгслийг нэрлэсэн үг хэллэгийн хэрэглээний тухай(Нийгэм хэл шинжлэлийн судалгаа)Хураангуй: Тус өгүүлэлд монгол хэлэнд буй адууг барих, бэхлэх, уях сойх, тэжээх арчлах, тэрэг, чарганд хөллөх тоног хэрэгслийг илтгэсэн үг, хэллэгийг нийгэм хэл шинжлэлийн асуулгын болон тооцооллын аргаар судлав. Уг судалгаанд бид 2021 онд Сүхбаатар аймгийн Асгат, Баяндэлгэр, Мөнххаан сум; 2022 онд Хэнтий аймгийн Батширээт, Дундговь аймгийн Цагаан дэлгэр сум, Увс аймгийн Өлгий сумын малчдын дунд малын тоног хэрэгслийг илтгэсэн үг хэллэгийн талаарх мэдлэг, малын тоног хэрэгслийн өнөөгийн хэрэглээний байдлын тухай судалгаа хийлээ. Мөн бид 2022 онд зах зээлд худалдан борлуулагдаж буй малын тоног хэрэгсэлтэй холбогдох үгийн сангийн хэрэглээний байдлыг тодруулах зорилгоор Улаанбаатар хотын Нарантуул олон улсын худалдааны төвд малын тоног хэрэгслийн худалдан борлуулагчдаас асуулга судалгаа авч, улмаар нүүр ном, unegui.mn зэрэг медиа хэрэглэгдэхүүн дэх малын тоног хэрэгсэл худалдан борлуулах зар, мэдээлэлд ажиглалт хийв. Ийнхүү судлахад малчдын тоног хэрэгслийг илтгэсэн үг хэллэгийн мэдлэг судалгаанд оролцогчдын амьдардаг бүс нутаг, нас зэрэг хүчин зүйлээрээ ялгаатай байгаа нь илрэв. Улмаар нийгмийн хөгжил дэвшилтэй холбоотойгоор тоног хэрэгслийг хийх хэрэглэх арга хэлбэр, материал зэргээс шалтгаалсан шинэ хэлбэрийн нэрлэлтүүд ч бий болсоор байгаа нь илрэв.Түлхүүр үг: aдууны тоног хэрэгсэл, нийгэм хэл шинжлэл, бүс нутаг, хэл хэрэглээ, хэлний амьдрал